What you know first - MacLachlan, Patricia; Moser, Barry (New York : HarperCollinsPublishers, 1998)
As a family prepares to move away from their farm, the daughter reflects on all the things she loves there so that when her baby brother is older she can tell him what it was like.
Reprint. Originally published: 1995.
Harper Trophy imprint on spine and p. [4] of cover.
"Joanna Cotler books."
NP
Keywords: Farm life -- Fiction; Country life -- Fiction; Moving -- Fiction